Determination of the Time of Sterilization and Water Dilution on the Processing of Palm Oil Using Oil Palm Loose Fruit as Raw Material - Adi Ruswanto; S Gunawan; I B B Partha; N Ngatirah (Oil Palm Research and Review, 2021)
The quality of raw materials, the process of sterilization of palm fruit, and the separation process of palm oil affect the productivity of the oil produced. The purpose of the study is to determine the time of sterilization of loose fruit and the amount of water dilution used against the properties of palm oil and the degree of separation of palm oil from the raw material of loose fruit. This study used a randomized complete design with 2 factors. The first factor of sterilization time consists of 4 levels; 30 minutes, 45 minutes, 60 minutes, 75 minutes. The second factor is the addition of hot water to the palm consisting of 3 levels: 100 %; 50 %; 0%. Further evaluated: percentage of oil separation, free fatty acid content, peroxide value. The data obtained is the analysis of variance (ANOVA) and if there is a different continued DMRT test 5%. Statistic analysis using SPSS version 25. The results showed that the treatment of sterilization time affects the free fatty acid content, separate oil percentages, peroxide value. The comparative treatment of the amount of water dilution affects the percentage of separate oils, peroxide value, free fatty acids. Based on the results of separate oil percentage analysis and free fatty acids, the sterilization treatment of oil palm loose fruit with a time of 30 minutes and a 50% dilution water is the best treatment.